2021
DOI: 10.1142/s0192415x21500749
|View full text |Cite
|
Sign up to set email alerts
|

Schisandra sphenanthera: A Comprehensive Review of its Botany, Phytochemistry, Pharmacology, and Clinical Applications

Abstract: Schisandra sphenanthera Rehd. et Wils (S. sphenanthera) is a single species of Schisandra genus, Magnoliaceae family, and it is a famous medicinal herb mostly growing in southern China, China Taiwan and Vietnam. S. sphenanthera is usually used for the treatments of hepatitis, Alzheimer’s disease, renal transplantation, osteoporosis, and insomnia. In present studies, approximately 310 natural constituents have been isolated from S. sphenanthera, including lignans, triterpenes, volatile oils, and polysaccharides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Schisandra sphenanthera is a popular traditional Chinese medicine used for the management of hepatitis, Alzheimer’s disease, renal transplantation, osteoporosis and insomnia [ 56 ]. Meanwhile, other closely related species, Schisandra chinensis can be found in many Western countries [ 57 ].…”
Section: Clinically Significant Pharmacokinetic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schisandra sphenanthera is a popular traditional Chinese medicine used for the management of hepatitis, Alzheimer’s disease, renal transplantation, osteoporosis and insomnia [ 56 ]. Meanwhile, other closely related species, Schisandra chinensis can be found in many Western countries [ 57 ].…”
Section: Clinically Significant Pharmacokinetic Interactionsmentioning
confidence: 99%
“…The ethanolic extract of Schisandra sphenanthera is commercially available and known as Wuzhi tablet. Compounds (lignans) isolated from Schisandra sphenanthera have demonstrated anti-inflammatory, immunomodulatory and anti-cancer properties [ 56 ]. Previous in vitro studies highlighted Schisandra lignans as substrates, inhibitors and inducers of CYP3A enzymes [ 57 ], although the predominant net clinical outcome following a chronic exposure to Schisandra sphenanthera extract appears to be CYP3A inhibition.…”
Section: Clinically Significant Pharmacokinetic Interactionsmentioning
confidence: 99%
“…We conducted a literature review of China's National Knowledge Infrastructure (CNKI) (https://www.cnki.net/) and Web of Science (https://www.webofscience.com/wos) and obtained 42 active compounds from S. chinensis. [21][22][23][24][25] (Table 1)…”
Section: Screening Of Chemical Compositionmentioning
confidence: 99%
“…Schisandra chinensis caulis polysaccharide (SCP) is the active ingredient in TCM schisandra chinensis, and studies have shown that it has anti-inflammatory, anti-oxidant, lipid-lowering and liver-protecting effects ( Huang et al, 2021 ). Feng et al (2021) used ultra-high-performance liquid chromatography-quadrupole/electrostatic field orbitrap high-resolution mass spectrometry (UHPLC-Q/Orbitrap-MS/MS) metabolomics method to analyze small molecule metabolites in NAFLD rat blood.…”
Section: Application Of Metabolomics In the Treatment Of Nafldmentioning
confidence: 99%